ENHANCING JOB PERFORMANCE: EXPLORING THE IMPACT OF PERSON-JOB FIT, JOB AUTONOMY, AND WORK-LIFE BALANCE - Wafin Mughniy Showa; Tri Wismiarsi; Muhril Ardiansyah (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
The examination in this research investigates the relationship between the employee’s performance to the person-job fit and job autonomy with work-life balance being the variable of interest. Using the quantitative method, data in forms of surveys were collected from 166 employees and analyzed in SmartPLS to check for correlation between the variables. The findings indicate that work life balance strengthens the link between both person job fit and job autonomy and job performance. It stresses that employees who are granted autonomy perform better and are more innovative whereas with work life balance lowers tension and enhances concentration and performance. This study encourages the managers to take into account both the workers’ preferences as well as the targets of the company in order to increase the level of effectiveness and motivation. It adds to the body of HR management by suggesting a practical approach to achieve a higher productivity of the office and to improve the living standards of its employees.